Does previous hypertension affect outcome in acute heart failure? - Felšöci, Marián; Pařenica, Jiří; Spinar, Jindřich; Vítovec, Jiří; Widimský, Petr; Linhart, Aleš; Fedorco, Marián; Málek, Filip; Cíhalík, Cestmír; Miklík, Roman; Jarkovský, Jiří (European journal of internal medicine, 2011)
BACKGROUND: The effect of previous long-term hypertension on mortality in acute heart failure (HF), regardless of blood pressure values, has not been well studied. METHODS: Acute Heart Failure Database (AHEAD) - Czech HF registry enrolled 4153 consecutive patients with acute HF. We excluded severe forms (cardiogenic shock, pulmonary oedema, right HF) and analysed 2421 patients with known presence or absence of previous hypertension. Demographic, clinical and laboratory profile, treatment and mortality rates were assessed and predictors of outcome were identified. RESULTS: Patients with previous hypertension (71.5%) were older, more of female gender, with worse pre-hospitalisation NYHA class, increased incidence of co-morbidities and higher left ventricular ejection fraction (LVEF). Although in-hospital mortality was similar in both cohorts (2.6%), survival at 1, 2 and 3-year was worse in the hypertensive group (75.6%, 65.9% and 58.7% vs. 80.7%, 74.2% and 69.8%; P<0.001). Nevertheless, hypertension was not associated with mortality in multivariate analysis and stronger predictors of outcome were identified (P<0.05): new-onset acute HF [hazard ratio (HR) 0.62] and increased body mass index (HR 0.68) proved to have a protective role. Advanced age (HR 1.86), diabetes (HR 1.45), lower LVEF (HR 1.28) and admission blood pressure (HR 1.54), elevated serum creatinine (HR 1.63), hyponatremia (HR 1.77) and anaemia (HR 1.40) were associated with worse survival. CONCLUSION: Antecedent hypertension is frequent in patients with acute HF and contributes to organ and vascular impairment. However its presence has no independent influence on short- and medium-term mortality, which is influenced by other related co-morbidities.
Keywords: Registries; Humans; Heart Failure; srdeční selhání; lidé středního věku; Hypertension; registrace; Predictive Value of Tests; rozložení podle pohlaví; Female; rizikové faktory; Aged; Hyponatremia; senioři; lidé; Diabetes Mellitus; věkové rozložení; ženské pohlaví; krevní tlak; Male; Middle Aged; prediktivní hodnota testů; hypertenze; incidence; dysfunkce levé srdeční komory; Incidence; Czech Republic; anemie; Aged, 80 and over; Anemia; Age Distribution; Ventricular Dysfunction, Left; Sex Distribution; senioři nad 80 let; hyponatremie; Česká republika; mužské pohlaví; Acute Disease; diabetes mellitus; Blood Pressure; akutní nemoc; Risk Factors